Berita Kunjungan Diplomatik sebagai Media Event di The Jakarta Post - NITA ANDRIANTI (Universitas Muhammadiyah Yogyakarta, 2014)
This study is about content analysis of diplomatic visits news as media event in The Jakarta Post. The approach in this research is quantitative descriptive with content analysis method. Content analysis method is known as a research method which is systematic and objective, and it tends to be more quantitative. The result indicates that mass media is a means of international communication in public diplomacy. Mass media as an instrument of public diplomacy has increased the positive image of Indonesia, supported the national objectives (eg: comprehensive partnership with the US), and supported the common goals for world establishment which is based on freedom, lasting peace, and social justice. However, this effort has not yet been accompanied by comprehensive understanding of mass media function as a medium of public diplomacy in political interaction and international communication, for example, a tendency of certain news that indicates mass media support towards the officials who visis Indonesia not the substance of bilateral relationship (advantages and disadvantages of the cooperation). Keywords: Diplomatic Visits, Media Agenda, The Jakarta Post, Content Analysis